2023
DOI: 10.1038/s41598-023-30630-y
|View full text |Cite
|
Sign up to set email alerts
|

Long-term high-fat diet increases glymphatic activity in the hypothalamus in mice

Abstract: Obesity affects millions of people worldwide and is associated with an increased risk of cognitive decline. The glymphatic system is a brain-wide metabolic waste clearance system, dysfunction of which is linked to dementia. We herein examined glymphatic transport in mice with long-term obesity induced by a high-fat diet for 10 months. The obese mice developed hypertension and elevated heart rate, neuroinflammation and gliosis, but not apparent systemic inflammation. Surprisingly, glymphatic inflow was globally… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 65 publications
2
6
0
Order By: Relevance
“…It could also be induced by T2DM-associated insulin resistance, as it is known that the suppression of insulin signalling in astrocytes leads to increased angiogenesis and altered blood flow [ 19 ]. Therefore, similar to what has been suggested for rodents on a long-term obesogenic diet [ 17 ], T2DM-associated insulin resistance may play a role in increased fluid trafficking in the hypothalamus in an Aq4-dependent manner. Another T2DM-associated pathological change that may contribute to the increased demand for clearance are disrupted circadian rhythms and impaired sleep quality, as adequate sleep quality ensures a sufficient removal of potentially neurotoxic waste products that accumulate in the awake central nervous system [ 55 ].…”
Section: Discussionsupporting
confidence: 70%
See 1 more Smart Citation
“…It could also be induced by T2DM-associated insulin resistance, as it is known that the suppression of insulin signalling in astrocytes leads to increased angiogenesis and altered blood flow [ 19 ]. Therefore, similar to what has been suggested for rodents on a long-term obesogenic diet [ 17 ], T2DM-associated insulin resistance may play a role in increased fluid trafficking in the hypothalamus in an Aq4-dependent manner. Another T2DM-associated pathological change that may contribute to the increased demand for clearance are disrupted circadian rhythms and impaired sleep quality, as adequate sleep quality ensures a sufficient removal of potentially neurotoxic waste products that accumulate in the awake central nervous system [ 55 ].…”
Section: Discussionsupporting
confidence: 70%
“…The role of Aq4 in the hypothalamus is still underexplored, although a recent study suggested increased activity of the glymphatic system in the hypothalamus in long-term high fat-fed mice [ 17 ]. Our findings regarding the increased numbers of Aq4-ir astrocytes in the hypothalamus of T2DM subjects may indicate an elevated need for microenvironmental clearance through the glymphatic system.…”
Section: Discussionmentioning
confidence: 99%
“…Present results suggest that transient changes in plasma osmolality due to fluctuating blood glucose levels induce PVS alterations that result in acceleration of glymphatic flow in the long-term. We have recently reported that a long-term high-fat diet in mice inducing severe obesity and hypertension did not alter brain-wide glymphatic fluid transport [ 53 ]. Thus, the glymphatic system may better accommodate chronic rather than repeated transient changes in physiological parameters.…”
Section: Discussionmentioning
confidence: 99%
“…However, a previous study found that the expression of AQP4 was significantly different in the cortex and hippocampus during postnatal and adulthood [ 60 ]. Meanwhile, long-term HFD challenge could increase AQP4 density and polarization in the hypothalamus, but not in the hippocampus [ 61 ]. Considering that there was no change in the number and area of astrocytes in the hippocampal region in PDGFB cTG and WT mice fed with CHD and HFD, different responses may occur in different brain subareas with respect to HFD challenge and persistent PDGF-BB elevation.…”
Section: Discussionmentioning
confidence: 99%